Teachers’ Contributions To The Inclusive Education Of Learners With Disabilities In The CEG Of Djougou (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to understand the difficulties faced by learners with disabilities in Djougou’s CEGs, and the contribution made by teachers in meeting their educational needs. To achieve this objective, we opted for qualitative research during which we interviewed 74 people, including : 22 students with disabilities, to find out about their experiences at school; 22 learners without disabilities, to find out about their perceptions of their peers with disabilities; and 30 teachers, from all disciplines, randomly selected from general secondary schools 1, 2 and 3 in the town of Djougou, to find out about teachers’ strategies and contributions to meeting the educational needs of learners with disabilities. The study revealed that learners with disabilities face enormous difficulties, which prevent them from fully enjoying their right to education. To this end, the role of the school community, in particular the teacher, remains multiple in the process of integrating these learners.